A novel biological activity for galectin-1: Inhibition of leukocyte-endothelial cell interactions in experimental inflammation - La, Mylinh; Cao, Thong V.; Cerchiaro, Graziela; Chilton, Kathya; Hirabayashi, Jun; Kasai, Ken-Ichi; Oliani, Sonia M. [UNESP]; Chernajovsky, Yuti; Perretti, Mauro (Elsevier, 2003)
Galectin-1 (Gal-1), the prototype of a family of β -galactoside-binding proteins, has been shown to attenuate experimental acute and chronic inflammation. In view of the fact that endothelial cells (ECs), but not human polymorphonuclear leukocytes (PMNs), expressed Gal-1 we tested here the hypothesis that the protein could modulate leukocyte-EC interaction in inflammatory settings. In vitro, human recombinant (hr) Gal-1 inhibited PMN chemotaxis and trans-endothelial migration. These actions were specific as they were absent if Gal-1 was boiled or blocked by neutralizing antiserum. In vivo, hrGal-1 (optimum effect at 0.3 μg equivalent to 20 pmol) inhibited interleukin-1β-induced PMN recruitment into the mouse peritoneal cavity. Intravital microscopy analysis showed that leukocyte flux, but not their rolling velocity, was decreased by an anti-inflammatory dose of hrGal-1. Binding of biotinylated Gal-1 to resting and post-adherent human PMNs occurred at concentrations inhibitory in the chemotaxis and transmigration assays. In addition, the pattern of Gal-1 binding was differentially modulated by PMN or EC activation. In conclusion, these data suggest the existence of a previously unrecognized function of Gal-1, that is inhibition of leukocyte rolling and extravasation in experimental inflammation. It is possible that endogenous Gal-1 may be part of a novel anti-inflammatory loop in which the endothelium is the source of the protein and the migrating PMNs the target for its anti-inflammatory action.
Keywords: galectin 1; antiinflammatory activity; cell compartmentalization; cell interaction; chronic inflammation; endothelium cell; experimental infection; extracellular matrix; extravasation; gene sequence; human; human cell; inflammatory cell; leukocyte; neutrophil; peritoneal cavity; priority journal; protein family; Animals; Binding Sites; Cell Communication; Cell Movement; Chemotaxis, Leukocyte; Dose-Response Relationship, Drug; Endothelium, Vascular; Flow Cytometry; Galectin 1; Humans; Injections; Interleukin-1; Interleukin-8; Leukocyte Rolling; Male; Mice; Neutrophils; Peritonitis; Recombinant Proteins